Credit Subsidy in Philippine Agriculture - Magdalena S. Casuga; Maria Piedad S. Geron (Philippine Institute for Development Studies (PIDS), 2012)
This study attempts to measure subsidies to agricultural credit in recent years and provides policy implications. It finds that credit policy has evolved, from provision of subsidized credit to one that is more market-oriented, focusing on providing access to credit to farmers while exposing them to market interest rates. Nevertheless, there remains a significant public outlay for credit largely through unintended default subsidy. It recommends that publicly supported credit be provided solely through competent government financial institutions under independent regulatory oversight, rather than through agencies (such as the Agricultural Credit Enhancement Fund) or through government-owned and controlled corporations (such as QUEDANCOR). Government may also need to invest in other support services that would attenuate agricultural risk and encourage greater private sector participation in agricultural lending.
Keywords: 330; Philippines; credit subsidy; market-oriented policy; default risk; risk reduction